EKSPLORASI ETNOMATEMATIKA PADA KERAJINAN KAYU DI DESA TUTUL KECAMATAN BALUNG SEBAGAI BAHAN AJAR GEOMETRI - Kholifatuzzuhro, Aina; Sunardi, Sunardi; Monalisa, Lioni Anka (Kadikma, 2020)
This study aims to explore anything ethnomatematics related to woodwork in Tutul Village, Jember. Woodcraft is a craft made from wood. This type of research is a study using a qualitative approach with ethnographic design. Research subjects in this study were craftsmen and owners of "Ara Collections" wood production houses. In this study the object is focused on bracelets, necklaces, and keeping. Based on the results of the study, it can be seen that wood crafts have mathematical elements. The mathematical elements found are ball, tube, cube, integrated cone, rectangular flat, circle, parabolic, ellipsoid, hyperbole, hyperbole, geometric patterns, reflection, dilation, and congruence and concordance. The teaching material made is in the form of a geometry test package related to ethnomatematics in wood crafts in Tutul Village, Balung Sub-District, Jember. Keywords: Ethnomatematics; Woodcraft; Geometry; Teaching Materials